1988
DOI: 10.1111/j.1442-9071.1988.tb01216.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Types of Primary Angle Closure Glaucoma

Abstract: There is no internationally adopted terminology for the clinical types of primary angle-closure glaucoma. Descriptions of three clinical types: 1. intermittent angle closure; 2. acute and subacute angle closure; and 3. creeping angle closure are presented with reasons for the division into and naming of these types. Chronic angle closure is not a distinct form but a late derivation from various types of angle closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 4 publications
1
44
0
Order By: Relevance
“…20 In our study, the refractive error calculated did not show any significant difference in the groups and the mean values were less than þ 1.0 D. But Grieten and Weekers 23 showed that eyes with angle closure glaucoma had anterior chambers 0.73 mm more shallow, corneal curvatures 0.20 mm less, and corneal diameters 0.48 mm smaller than eyes of the same age with the same degree of hypermetropia. Lowe 4 noted that eyes with PACG are mostly hypermetropic; nevertheless, some are also myopic, so that hypermetropia is insufficient to explain the anatomical conditions that lead to angle closure glaucoma.…”
Section: Eyementioning
confidence: 99%
See 1 more Smart Citation
“…20 In our study, the refractive error calculated did not show any significant difference in the groups and the mean values were less than þ 1.0 D. But Grieten and Weekers 23 showed that eyes with angle closure glaucoma had anterior chambers 0.73 mm more shallow, corneal curvatures 0.20 mm less, and corneal diameters 0.48 mm smaller than eyes of the same age with the same degree of hypermetropia. Lowe 4 noted that eyes with PACG are mostly hypermetropic; nevertheless, some are also myopic, so that hypermetropia is insufficient to explain the anatomical conditions that lead to angle closure glaucoma.…”
Section: Eyementioning
confidence: 99%
“…[1][2][3][4] Certain racial groups are at an increased risk of developing PACG. [5][6][7][8][9] A positive family history of PACG is an additional risk factor.…”
Section: Introductionmentioning
confidence: 99%
“…8 However, symptoms appear not to be a good indicator of glaucomatous visual loss: 60-75% of persons suffering an acute episode of PAC recover without optic disc or visual field damage, at least in the short term. 9,10 The majority of Asian people suffering from angleclosure experience no symptoms.…”
Section: Definition and Classificationmentioning
confidence: 99%
“…They maintained that their results might provide ex perimental support for the theory of direct lens block as an angle-closure mechanism. Creeping angle-closure glauco ma is uncommon in Caucasians but is much more prevalent in Chinese and those races with similar eyes [5][6][7]. Al though iridectomy will eliminate the component of pupil lary block in creeping angle-closure glaucoma, raised in traocular pressure (IOP) is likely to persist and needs further management [6,7].…”
mentioning
confidence: 99%